Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Quantifying soil organic matter stock distribution and origin following over a century of maize-based cropping in the former tallgrass prairie region of central USA - Yuhei Nakayama; Michael D. Masters; Evan H. DeLucia; Andrew J. Margenot (Agriculture, Ecosystems & Environment, 2026)

Ref-1 is overexpressed in neovascular eye disease and targetable with a novel inhibitor - Anbukkarasi Muniyandi; Gabriella D. Hartman; Kamakshi Sishtla; Ratan Rai; Cátia Gomes; Kristina Day; Yang Song; Andi R. Masters; Sara K. Quinney; Xiaoping Qi; Hailey Woods; Michael E. Boulton; et al. (Angiogenesis, 2025)

Association of Sport Helmet Status on Concussion Presentation and Recovery in Male Collegiate Student-Athletes - Adrian J. Boltz; Landon B. Lempke; Reid A. Syrydiuk; Stefan Duma; Paul Pasquina; Thomas W. McAllister; Michael McCrea; Avinash Chandran; Steven P. Broglio; Louise Kelly; Justus Ortega; Nicholas Port; et al. (Annals of Biomedical Engineering, 2024)

Female Collegiate Athletes’ Concussion Characteristics and Recovery Patterns: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Jaclyn B. Caccese; Reid A. Syrydiuk; Thomas A. Buckley; Sara P. D. Chrisman; James R. Clugston; James T. Eckner; Elsa Ermer; Carrie Esopenko; Divya Jain; Louise A. Kelly; Allyssa K. Memmini; et al. (Annals of Biomedical Engineering, 2024)

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

The Kalahari sediments and hominins in southern Africa - A. Matmon; S. Vainer; A. Hidy; A. Kuzmenko; Frank Eckardt; S. Master; M. Wendorff; M. De Wit; M. Shaw; A.S.T.E.R. Team; D. Fink; M. Chazan (Quaternary Science Reviews, 2024)

Constraints on mineral-associated and particulate organic carbon response to regenerative management: carbon inputs and saturation deficit - Alison E. King; Joseph P. Amsili; S. Carolina Córdova; Steve Culman; Steven J. Fonte; James Kotcon; Michael D. Masters; Kent McVay; Daniel C. Olk; Aaron M. Prairie; Meagan Schipanski; Sharon K. Schneider; et al. (Soil and Tillage Research, 2024)

Validating assumptions in calculating carbon dioxide removal by enhanced rock weathering in Kantola et al., 2023 - Adam Wolf; Elliot Chang; Ilsa B. Kantola; Elena Blanc‐Betes; Michael D. Masters; Alison Marklein; Caitlin E. Moore; Carl J. Bernacchi; Evan H. DeLucia (Global Change Biology, 2024)

Improved net carbon budgets in the US Midwest through direct measured impacts of enhanced weathering - Ilsa B. Kantola; Elena Blanc‐Betes; Michael D. Masters; Elliot Chang; Alison Marklein; Caitlin E. Moore; Adam von Haden; Carl J. Bernacchi; Adam Wolf; Dimitar Z. Epihov; David J. Beerling; Evan H. DeLucia (Global Change Biology, 2023)
Terrestrial enhanced weathering (EW) through the application of Mg‐ or Ca‐rich rock dust to soil is a negative emission technology with the potential to address impacts of climate change. The effectiveness of EW was tested over 4 years by spreading ground basalt (50 t ha −1 year −1 ) on maize/soybean and miscanthus cropping systems in the Midwest US. The major elements of the carbon budget were quantified through measurements of eddy covariance, soil carbon flux, and biomass. The movement of Mg and Ca to deep soil, released by weathering, balanced by a corresponding alkalinity flux, was used to measure the drawdown of CO 2 , where the release of cations from basalt was measured as the ratio of rare earth elements to base cations in the applied rock dust and in the surface soil. Basalt application stimulated peak biomass and net primary production in both cropping systems and caused a small but significant stimulation of soil respiration. Net ecosystem carbon balance (NECB) was strongly negative for maize/soybean (−199 to −453 g C m −2 year −1 ) indicating this system was losing carbon to the atmosphere. Average EW (102 g C m −2 year −1 ) offset carbon loss in the maize/soybean by 23%–42%. NECB of miscanthus was positive (63–129 g C m −2 year −1 ), indicating carbon gain in the system, and EW greatly increased inorganic carbon storage by an additional 234 g C m −2 year −1 . Our analysis indicates a co‐deployment of a perennial biofuel crop (miscanthus) with EW leads to major wins—increased harvested yields of 29%–42% with additional carbon dioxide removal (CDR) of 8.6 t CO 2 ha −1 year −1 . EW applied to maize/soybean drives a CDR of 3.7 t CO 2 ha −1 year −1 , which partially offsets well‐established carbon losses from soil from this crop rotation. EW applied in the US Midwest creates measurable improvements to the carbon budgets perennial bioenergy crops and conventional row crops.

Prevalence of Food Insecurity and Association with Depression Among Graduate Students at an Urban University - K. Bell; A. Hollenbeck; M. Masters; J. Lunsford; L. Pollitt; K. Whitson; D. Mccutcheon (Journal of the Academy of Nutrition and Dietetics, 2023)

Microorganisms, their residues, and soil carbon storage under a continuous maize cropping system with eight years of variable residue retention - Xuefeng Zhu; Hongtu Xie; Michael D. Masters; Yichao Rui; Yu Luo; Hongbo He; Xudong Zhang; Chao Liang (Applied Soil Ecology, 2023)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A naturalistic study of orally administered vs. inhaled legal market cannabis: cannabinoids exposure, intoxication, and impairment - L. Cinnamon Bidwell; Hollis C. Karoly; Marco Ortiz Torres; Ashley Master; Angela D. Bryan; Kent E. Hutchison (Psychopharmacology, 2022)

Commonality of adherent-invasive Escherichia coli isolated from patients with extraintestinal infections, healthy individuals and the environment - D. J. Astley; N. Masters; A. Kuballa; M. Katouli (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Analysis of Bisulfite Via a Nitro Derivative of Cyanine-3 (NCy3) in the Microfluidic Channel - Haley A. Houtwed; Meng Xie; Aatiya Ahmad; Cody D. Masters; Melissa M. Davison; Kristy Kounovsky-Shafer; Haishi Cao (Journal of Fluorescence, 2019)

Root volume distribution of maturing perennial grasses revealed by correcting for minirhizotron surface effects - Christopher K. Black; Michael D. Masters; David S. LeBauer; Kristina J. Anderson-Teixeira; Evan H. DeLucia (Plant and Soil, 2017)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Acute temperature sensitivity in optic nerve axons explained by an electrogenic membrane potential - Tom A. Coates; Oscar Woolnough; Joseph M. Masters; Gulsum Asadova; Charmilie Chandrakumar; Mark D. Baker (Pflügers Archiv - European Journal of Physiology, 2015)

Conservation gone to the dogs: when canids rule the beach in small coastal reserves - Thomas A. Schlacher; Michael A. Weston; David Lynn; David S. Schoeman; Chantal M. Huijbers; Andrew D. Olds; Sam Masters; Rod M. Connolly (Biodiversity and Conservation, 2015)

Altered Belowground Carbon Cycling Following Land-Use Change to Perennial Bioenergy Crops - Kristina J. Anderson-Teixeira; Michael D. Masters; Christopher K. Black; Marcelo Zeri; Mir Zaman Hussain; Carl J. Bernacchi; Evan H. DeLucia (Ecosystems, 2013)

Prevalence of β-thalassemia and other haemoglobinopathies in six cities in India: a multicentre study - D. Mohanty; R. B. Colah; A. C. Gorakshakar; R. Z. Patel; D. C. Master; J. Mahanta; S. K. Sharma; U. Chaudhari; M. Ghosh; S. Das; R. P. Britt; S. Singh; et al. (Journal of Community Genetics, 2013)

Comparison of Global Mean Sea Level Time Series from TOPEX/Poseidon, Jason-1, and Jason-2 - D. Masters; R. S. Nerem; C. Choe; E. Leuliette; B. Beckley; N. White; M. Ablain (Marine Geodesy, 2012)

Sequence analysis of RNA 2 and RNA 3 of lilac leaf chlorosis virus: a putative new member of the genus Ilarvirus - D. James; A. Varga; L. Leippi; S. Godkin; C. Masters (Archives of Virology, 2010)

Summer drought alters plant‐mediated competition between foliar‐ and root‐feeding insects - JOANNA T. STALEY; SIMON R. MORTIMER; MICHAEL D. MORECROFT; VALERIE K. BROWN; GREGORY J. MASTERS (Global Change Biology, 2007)
Summer droughts are predicted to increase in severity and frequency in the United Kingdom, due to climate change. Few studies have addressed the impacts of drought on interactions between species, and the majority have focussed on increases in CO 2 concentration and changes in temperature. Here, the effect of experimental summer drought on the strength of the plant‐mediated interaction between leaf‐mining Stephensia brunnichella larvae and root‐chewing Agriotes larvae was investigated. Agriotes larvae reduced the abundance and performance of S. brunnichella feeding on a mutual host plant, Clinopodium vulgare , as well as the rate of parasitism of the leaf‐miner. The interaction did not, however, occur on plants subjected to a severe drought treatment, which were reduced in size. Changes to summer rainfall, due to climate change, may therefore reduce the occurrence of plant‐mediated interactions between insect herbivores.

Methionine oxidation: Implications for the mechanism of toxicity of the β-amyloid peptide from Alzheimer's disease - Giuseppe D. Ciccotosto; Kevin J. Barnham; Robert A. Cherny; Colin L. Masters; Ashley I. Bush; Cyril C. Curtain; Roberto Cappai; Deborah Tew (International Journal of Peptide Research and Therapeutics, 2003)

Copper Modulation of Ion Channels of PrP[106–126] Mutant Prion Peptide Fragments - J. I. Kourie; B. L. Kenna; D. Tew; M. F. Jobling; C. C. Curtain; C. L. Masters; K. J. Barnham; R. Cappai (The Journal of Membrane Biology, 2003)

Herbivory in global climate change research: direct effects of rising temperature on insect herbivores - Jeffery S. Bale; Gregory J. Masters; Ian D. Hodkinson; Caroline Awmack; T. Martijn Bezemer; Valerie K. Brown; Jennifer Butterfield; Alan Buse; John C. Coulson; John Farrar; John E. G. Good; Richard Harrington; et al. (Global Change Biology, 2002)
This review examines the direct effects of climate change on insect herbivores. Temperature is identified as the dominant abiotic factor directly affecting herbivorous insects. There is little evidence of any direct effects of CO 2 or UVB. Direct impacts of precipitation have been largely neglected in current research on climate change. Temperature directly affects development, survival, range and abundance. Species with a large geographical range will tend to be less affected. The main effect of temperature in temperate regions is to influence winter survival; at more northerly latitudes, higher temperatures extend the summer season, increasing the available thermal budget for growth and reproduction. Photoperiod is the dominant cue for the seasonal synchrony of temperate insects, but their thermal requirements may differ at different times of year. Interactions between photoperiod and temperature determine phenology; the two factors do not necessarily operate in tandem. Insect herbivores show a number of distinct life‐history strategies to exploit plants with different growth forms and strategies, which will be differentially affected by climate warming. There are still many challenges facing biologists in predicting and monitoring the impacts of climate change. Future research needs to consider insect herbivore phenotypic and genotypic flexibility, their responses to global change parameters operating in concert, and awareness that some patterns may only become apparent in the longer term.

Mitochondrial Sequences as Indicators of Genetic Classification in Bush Babies - M. DelPero; J. C. Masters; D. Zuccon; P. Cervella; S. Crovella; G. Ardito (International Journal of Primatology, 2000)

Threats to Imperiled Freshwater Fauna - Brian D. Richter; David P. Braun; Michael A. Mendelson; Lawrence L. Master (Conservation Biology, 1997)
Threats to imperiled freshwater fauna in the U.S. were assessed through an experts survey addressing anthropogenic stressors and their sources. Specifically, causes of historic declines and current limits to recovery were identified for 135 imperiled freshwater species of fishes, crayfishes, dragonflies and damselflies, mussels, and amphibians. The survey was designed to identify threats with sufficient specificity to inform resource managers and regulators faced with translating information about predominant biological threats into specific, responsive actions. The findings point to altered sediment loads and nutrient inputs from agricultural nonpoint pollution; interference from exotic species; and altered hydrologic regimes associated with impoundment operations as the three leading threats nationwide, accompanied by many lesser but still significant threats. Variations in threats among regions and among taxa were also evident. Eastern species are most commonly affected by altered sediment loads from agricultural activities, whereas exotic species, habitat removal/damage, and altered hydrologic regimes predominate in the West. Altered sediment loading from agricultural activities and exotic species are dominant problems for both eastern mussels and fishes. However, eastern fishes also appear to be suffering from municipal nonpoint pollution (nutrients and sediments), whereas eastern mussels appear to be more severely affected by altered nutrient impacts from hydroelectric impoundments and agricultural runoff. Our findings suggest that control of nonpoint source pollution associated with agriculture activities should be a very high priority for agricultural producers and governmental support programs. Additonally, the large number of hydropower dams in the U.S. subject to federal re‐licensing in coming years suggests a significant opportunity to restore natural hydrologic regimes in the affected rivers.